Piezoelectric performance improvement via macromolecular rearrangement. (1st November 2022) - Meng, Qingyu; Jin, Wenjing; Zhang, Zhuo; Zhang, Minghao; Shen, Xiaoping; Zhou, Zhu; Sun, Qingfeng
Abstract: Because of their good flexibility and capacity to capture the dynamic mechanical energy by converting it into electrical signals, polymeric piezoelectric nanogenerators (PENGs) have broad application prospects in mechanical vibration detection and acquisition as sensors and self-powered systems. Here, a flexible PENG film based on hydroxypropyl cellulose (HPC) as the matrix, polyvinylidene fluoride (PVDF) as an auxiliary electrospinning reagent and BaTiO3 nanoparticles (NPs) as a piezoelectric nanofiller is constructed by electrospinning and post-treatments for macromolecule rearrangement and thus piezoelectricity enhancement. This PENG demonstrates a superior sensitivity (23.33 mV kPa −1 ) which is over 3.9 times those of the commercial PVDF and polyvinylidene fluoride-trifluoroethylene films. This performance enhancement is ascribed to the HPC dissolution and regeneration during post-treatments, resulting in the formation of outer wrappers around fibrils and thus an interconnected fibrous network with junction nodes between adjacent fibers for stress transfer efficiency. The partial crystal phase transformation of PVDF during film densification may also play a role in the increase of piezoelectricity. A series of practical application scenarios are established to demonstrate the highly promising potential of this fibril-based composite membrane for multifunctional force sensing and energy collection.